'Transforming' children's services? : social work, neoliberalism and the "Modern" world - Garrett, Paul Michael , 1958- (Maidenhead, England : Open University Press, 2009)
Transforming Children's Services will be a vital text for social work and social policy students. Furthermore, the book directly addresses a range of issues of direct concern to practitioners
1. Introduction -- 2. Theorizing neoliberal transformation -- 3. The 'transformational reform agenda': the Change for Children programme -- 4. Neoliberal globalism, 'race' and place: reviewing the Laming Report on the death of Victoria Climbie? -- 5. 'Transformation', technology and surveillance -- 6. Making 'anti-social behaviour': ASBO politics -- 7. 'Problem families' and 'sinbin' solutions -- 8. Making 'happier' children and more 'fulfilled' social workers? Privatizing social work services for 'looked after' children -- 9. Conclusion
Includes bibliographical references and index
Keywords: Child welfare -- England; Children -- Service for -- England; Social work with children -- England